Pengaruh Irigasi Defisit terhadap Pertumbuhan dan Produksi Melon (Cucumis melo. L) Varietas Sky Rocket - Ridwan, Ridwan; Mazidah, Mazidah; Amien, Elhamida Rezkia; Asmara, Sandi; Oktafri, Oktafri (Jurnal Agricultural Biosystem Engineering, 2024)
Melon (Cucumis melo L.) plants have high economic value and require optimal water management to support growth and production. This study aims to analyze the effects of deficit irrigation on water requirements, growth, and yield of melon plants. The research was conducted using a Completely Randomized Design (CRD) with four levels of deficit irrigation treatments (100%, 80%, 60%, and 40% of field capacity) and six replications. The results showed that 80% deficit irrigation could maintain optimal growth and produce yields equivalent to full irrigation (100%), whereas 60% and 40% deficit irrigation caused significant water stress, hindering growth and reducing yields. Therefore, 80% deficit irrigation is recommended as a water management strategy for melon cultivation, especially in areas with limited water availability. Keywords: Cucumis melo, Deficit Irrigation, Growth, Yield, Water Management.